Designing a Nodemcu Based Fire Detection System Using Map and Telegram Applications - Fajar, Muhammad; Sardi, Juli (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Fire is the emergence of a fire that is not controlled and is very difficult for humans to control, which results in a fatal impact in the form of material losses, namely property and human casualties. So in this study a fire detection system in a house or building based on NodeMCU ESP8266 and a map application using Iot that will work when the sensor detects a fire so that it can find the location where there is a fire so that it can find the location of the fire through the application. The system is built using Arduino type NodeMCU ESP2866 as a control center, fire sensor as a telegram application detector as a fire message sender and NEO-6 GPS module as a location tracker where the fire occurred. The output of this system is a fire information message on the system owner's number. The results of the research obtained are from the design and testing of the tool in general the system can work in accordance with the design of a fire detector using NodeMCU ESP8266, the designed system can send location coordinates in the form of (google Mapsi) or notification in the form of a fire warning to the homeowner through the telegram application and the system that has been designed can send information.